Association of arbuscular mycorrhizal fungi in certain medicinal plants of Apocynaceae and Asclepiadaceae - and C. MANOHARACHARY*, S. SWARUPA RANI (Indian Phytopathology, 2007)
Thirty one host plants belonging to Apocynaceae and Asclepiadaceae were screened for arbuscular mycorrhizal (AM) fungal association in their rhizosphere soils. All plants which were either medicinal or ornamental were found harbouring AM fungi. 48 fungal species representing Acaulospora, Archaeospora, Entrophospora, Gigaspora, Glomus, Scutellospora and SClerocystis were encountered. Glomus with 28 species was the predominant genus. All the host plants surveyed form new host record for AM fungi in India.